BackTrack 5 wireless penetration testing : beginner's guide : master bleeding edge wireless testing techniques with BackTrack 5 - Ramachandran, Vivek (Packt Pub., 2011)
Master bleeding edge wireless testing techniques with BackTrack 5.
"Learn by doing: less theory, more results"--Cover.
Includes index.
Keywords: Computers -- Access control.; Penetration testing (Computer security); Computer networks -- Security measures -- Testing.; elektronické knihy; electronic books